Makna Langit dan Bumi Baru dalam Wahyu 21:1 Tentang Harapan Eskatologis - Prengky Ishak (Vieka Wahana Semesta, 2026)
Revelation 21:1 is one of the biblical texts that presents eschatological hope through the imagery of “a new heaven and a new earth.” This passage is often misunderstood as a description of believers escaping from the world into heaven, leading to a neglect of earthly reality. Therefore, this article aims to examine the theological meaning of Revelation 21:1 by emphasizing the concept of the renewal of creation as the core of Christian eschatological hope. This study employs a qualitative method through a literature review of Indonesian theological journals that discuss the Book of Revelation, particularly from theological, socio-political, and symbolic perspectives. The study finds that Revelation 21:1 does not describe the total destruction of the world, but rather the complete restoration of creation that has been damaged by sin and injustice. The expressions “the first heaven and the first earth have passed away” and “the sea was no more” are understood symbolically as the end of the old order characterized by suffering, chaos, and oppression. Furthermore, this text reflects the fulfillment of Old Testament promises and serves as encouragement for early Christian communities living under social and political pressure during the Roman Empire. Thus, Revelation 21:1 presents an eschatological hope that is active and contextual, rather than an escape from worldly reality. This hope calls believers to remain faithful and persevering while viewing the future as the total restoration of creation under God’s sovereign reign.